Labour-related Dispute Settlement under the United States’ Free Trade Agreements and Recommendations for Vietnam - Ngoc Ha, Nguyen (VNU Journal of Science: Legal Studies, 2023)
Many United States’ free trade agreements, including the new generation of free trade agreements, contain strong commitments on labor, especially from a dispute settlement perspective. There are concerns about the effectiveness of such labor dispute resolution mechanisms. However, the practice of settling disputes between the United States and its partners has partly shown that these mechanisms have worked quite well to quickly resolve problems and disagreements between the parties during the implementation of their labor commitments. This can help Vietnam draw some meaningful lessons. Therefore, this article will focus on analyzing some key points in the labor dispute settlement mechanisms, the practical use of this mechanism in free trade agreements to which the United States is a member and on drawing some lessons for Vietnam